1998
DOI: 10.1038/sj.sc.3100627
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and anaerobic arm-cranking power outputs of males with lower limb impairments: Relationship with sport participation intensity, age, impairment and functional classification

Abstract: Fifty individuals with lower limb impairments including spinal cord injury, polio and amputations underwent aerobic and anaerobic arm-cranking tests in a standardized laboratory setting. Based on linear regression models applied with age as dependent variable aerobic performance variable including HRmax (R=0.395, P=0.004), and POaer (R=0.31, P=0.021) were subjected to ANCOVA adjusting for age in order to determine the signi®cance of participation intensity (competitive vs leisure) and type of physical impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 20 publications
4
34
0
6
Order By: Relevance
“…Many authors have also assessed the relationship between the performance level of wheelchair basketball players and their classification level [9,10,12,15,16]. De Lira et al [9] investigated aerobic and anaerobic performance in a homogenous sample of players and showed correlations between their functional classification level and aerobic capacity (peak oxygen -VO 2 peak) and anaerobic performance (peak power output, relative peak power output, and mean power output).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have also assessed the relationship between the performance level of wheelchair basketball players and their classification level [9,10,12,15,16]. De Lira et al [9] investigated aerobic and anaerobic performance in a homogenous sample of players and showed correlations between their functional classification level and aerobic capacity (peak oxygen -VO 2 peak) and anaerobic performance (peak power output, relative peak power output, and mean power output).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that PWC in individuals with SCI is in¯uenced by these factors (Hutzler et al 1998;Noreau and Shephard 1992;Yamasaki et al 1998) as well as factors unique to individuals with SCI, such as the level of SCI (Burkett et al 1990;Drory et al 1990;Irizawa et al 1994) and the period since SCI (Janssen et al 1996;Yarkony et al 1988). Thus, PWC in individuals with SCI is in¯uenced by more factors compared with that in able-bodied persons.…”
Section: Introductionmentioning
confidence: 99%
“…However, most equipment disregards the movement ergonomics 2 , have oversized 3,4 and complex calibrations 5 , and are restricted to therapeutic analysis laboratories. Recently, Oliveira et al 6 developed and validated a compact roller dynamometer to evaluate wheelchair propulsion using a simple, small device.…”
Section: Introductionmentioning
confidence: 99%